(3GdehShYI GdTGedI ddMjhGfGJs (3GdRhGMa hGdHQeGFjGJs ((3HjQhJs (3GdeSJbHd GdQbejs, 2013)
(3GdOdjd GdeQFj dYGe GdMjGI GdHQjI MjK GdeYQaI dG MOhO dgG(B. (3JVe GdehShYI CcKQ ef (B2000 (3fhY ef GdMjhGfGJ dcd fhY NUGFK heejRGJ QJHJ Vef edaGJ ZfjII HGdeYdheGJ dJchf eQLYkG TGedkG ddOGQSjf hGdHGMKjf hGdWdGH(B. (3ebOeI eaUdI Yf JTQjM GdMjhGfGJ hOhQGJ GdMjGI hJUfjaGJgG(B. (3GSJYQGV ePgd dehGWf GdMjhGfGJ hJcjagG eY GdHjFI GdeMjWI HgGs
2
Keywords: Aquatic ecology; (3GdcGFfGJ GdMjIs